Aging Voice - Makiyama, Kiyoshi; Hirano, Shigeru (Springer Singapore : Imprint: Springer, 2017)
This book discusses the aging voice, one of the interesting issues related to aging. Population aging is an issue in most developed countries, where both physicians and specialists are required to improve clinical and scientific practice for elderly adults. In particular, the need for expertise in the diagnosis and treatment of aging voice pathologies is increasing continually. New developments in regenerative medicine have taken care for the aging voice to new level, and the contributors to this book use their wealth of experience in the field of the aging voice to present the latest advances in this field. This book is a unique resource, providing new perspectives for physicians, clinicians and health care workers who are interested in the aging voice.